Soft Law in International Trade Finance : A Comparative Analysis of the Harmonizing Effect of the UCP - Gama Jr., Lauro; Oliveira, Agatha Brandão de; Saumier, Geneviève (International Law E-Books Online, Collection 2025., 2024)
Expert contributors to this volume offer a comprehensive exploration of the UCP 600's impact on international trade finance law, examining the dynamic interplay between soft law and legal harmonization in 28 jurisdictions across all continents. With a rich array of case studies and insightful analysis, this book provides a nuanced interpretation of how soft law shapes global commerce. Its diverse perspectives and practical insights make it essential reading for practitioners and scholars seeking a deeper understanding of the real-world implications of soft law in trade.